THE SINGAPORE APPROACH TO HUMAN STEM CELL RESEARCH, THERAPEUTIC AND REPRODUCTIVE CLONING - Kian, Catherine Tay Swee (Bioethics, 2005)
With the controversial ethical issues on the creation of human embryos through cloning for therapeutic research, which holds more promise for medical breakthroughs that the world could ever imagine and the acknowledgement by many scientists that this biotechnology may not lead in the near future to therapies; this country report discusses the approach Singapore takes on human stem cell research, interjected with the authors’ own arguments and suggestions especially on research compensation injuries, an often neglected important issue. International comparative viewpoints taken by the major countries in the world are also included in the appendix.